Kinematics 2017
DOI: 10.5772/intechopen.71418
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Biodynamic Model of the Long Jump Technique

Abstract: The main aim of the study was to determine the kinematic model for long jump and define the kinematic and dynamic parameters of an elite long jumper's technique. The theoretical model was based on real data where the jumper was defined with a joint mass point. In view of certain previous similar studies, our study identified kinematic and dynamic parameters directly without using the inverse mechanics method. The analysis was made on two jumps of the top level athlete G.C., who won the bronze medallion in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The present study confirms that the EHS were distinguished from the ED by their shorter stride length over the hurdle, lower CM path, and faster crossing technique. Čoh et al [35] found that elite athletes with shorter hurdle clearance times had faster hurdle running times. According to McDonald and Dapena [10], the criterion of an efficient hurdle clearance technique is the shortest possible time of the flight phase (hurdle clearance time); otherwise, the hurdler loses velocity in the air.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study confirms that the EHS were distinguished from the ED by their shorter stride length over the hurdle, lower CM path, and faster crossing technique. Čoh et al [35] found that elite athletes with shorter hurdle clearance times had faster hurdle running times. According to McDonald and Dapena [10], the criterion of an efficient hurdle clearance technique is the shortest possible time of the flight phase (hurdle clearance time); otherwise, the hurdler loses velocity in the air.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative analysis of the angular kinematics reveals that the EHS are distinguished by a more pronounced forward slope of the trunk at hurdle-crossing, particularly during the landing phase. This body posture at the landing phase creates auspicious conditions for an active landing after hurdle-crossing, minimising the loss of speed mainly during the amortisation phase, ensuring easier forward locomotion [35], and allowing the CM to lower to an optimal level above the hurdle [2]. It should also be noted that the EHS show more efficient movement of the attacking leg at the moment of propulsion and hurdle attack.…”
Section: Discussionmentioning
confidence: 99%
“…Running speed was measured using Cronox 2.0 (Madrid, Spain). To assess students' studies, there were selected indicators that characterize the long jump technique: long jump (cm); speed of the last 5 m of running start (m/s); speed of the last 10 m running start (m/s); take-off time (m/s); tempo of the last six steps (step/s) [22,23]. Indicators were obtained by analyzing video records of long jumps at the beginning and end of the research.…”
Section: Methodsmentioning
confidence: 99%
“…These actions will contribute to optimally increasing 400-m performance in elite and sub-elite sprinters. One of the main factors determining the effectiveness of the 400-m sprint is the athletes' speed level (Bergamini, 2011;Brüggemann et al, 1999;Čoh et al, 1995). The abovementioned factor is directly related to the length and frequency of steps and the optimal time of foot contact with the ground (Mackala and Fostiak, 2015;Mackala et al, 2019;Maćkała and Mero, 2013).…”
Section: Introductionmentioning
confidence: 99%